La liberté du double cadre - Vincent Amiel (Images Re-Vues)
In his film The Passenger, which recounts the quest for an impossible freedom, Antonioni multiplies the frames within the frame, up to a famous shot that has become legendary, which underlines and erases the power of the frames.